The attitudes of EPS instructors towards using instructional technology in their classes - Eyyam, Ramadan; Menevis, Ipek; Dogruer, Nazan (Elsevier Science Bv, 2010)
This study aims to find out the attitudes of EPS full-time instructors at Eastern Mediterranean University (EMU), Famagusta, North Cyprus, towards the use of instructional technology - such as computers, Over Head Projectors (OHP), data projector, CD player, video, etc. - in their classes during the 2009-2010 Academic Year Fall Semester. For this reason, a questionnaire which identifies teachers' attitudes towards instructional technology with Likert Scale was prepared. The data was analyzed using SPSS Statistical Program. Although, instructors have positive attitudes towards the use of instructional technology in their classes, they need more information about the use of it. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Instructional technologies; attitude; preparatory school instructors; attitude scale